Comparison of Direct Oral Anticoagulants for Treatment of Cerebral Venous Thrombosis – A Retrospective Cohort Study - Paul Phan PharmD; Lisa T. Hong PharmD, BCPS, APh, PNAP (Clinical and Applied Thrombosis/Hemostasis)
Limited available evidence comparing DOACs with warfarin suggests efficacy and safety of DOACs for CVT. We aimed to evaluate whether a specific DOAC is preferred for the treatment of CVT. This retrospective cohort study included adult patients with CVTs between September 2018 and September 2022 treated with a DOAC. The primary outcome was rate of partial or complete recanalization. Secondary outcomes included rate of recurrent VTE, CVT extension, major or clinically relevant non-major bleeding, and death within 180 days after DOAC initiation. Of 31 patients with CVT, 21 received apixaban, 7 received rivaroxaban, and 3 received dabigatran. Among those with repeat imaging, the primary composite outcome occurred in 100%, 80%, and 100% for each group, respectively (P = 0.34). One patient had extension of CVT while on apixaban and one patient had increased midline shift while on rivaroxaban. No other secondary outcomes were observed. There do not appear to be significant efficacy or safety differences between DOACs when used for CVT treatment, though larger studies are needed to validate these findings.